TARDBP p.I383V, a recurrent alteration in Greek FTD patients - Charoniti,E.; Papastefanopoulou,V.; Florou-Hatziyiannidou,C.; Koros,C.; Stanitsa,E.; Papatriantafyllou,J.D.; Papageorgiou, S.G.; Kroupis, C. (J.Neurol.Sci., 2021)
BACKGROUND: A significant proportion of FTD (Frontotemporal Degeneration) cases can be attributed to mutations in major genes such as GRN, MAPT and C9orf72. Our previous report on a Greek FTD cohort revealed the presence of the single nucleotide polymorphism (SNP) p.I383V (rs80356740) in the TARDBP gene in three unrelated patients. Our objective was to develop a novel, fast and accurate method for the detection of this particular SNP and evaluate the assay in a larger cohort. METHODS AND RESULTS: A real-time qPCR-melting curve analysis method was developed, validated and tested in 142 FTD patients and 111 healthy control subjects. The SNP was detected in another two patients raising its yield in FTD patients to 3.5% (5 out of 142 patients) while one in 111 healthy controls was found to be a carrier. However, its frequency in the general population has been reported extremely low in international SNP databases (0.002%). CONCLUSION: This fact along with the indicated pathogenicity of this SNP in some bioinformatics tools, suggest that TARDBP p.I383V is recurrent and likely pathogenic for the Greek FTD population. Our high-throughput method could be used for genotyping in other larger patient cohorts and in other populations. Additionally, functional in vitro studies are required for the final adjudication of this TARDBP alteration as a pathogenic alteration
Keywords: Biological Assay; DNA-Binding Proteins; Frontotemporal Dementia; genetics; Greece; Humans; Mutation